EFFECT OF SKILL KINEMATIC EXERCISES ACCORDING TO NEURAL BRAIN PROGRAMMING TO DEVELOPING MOTOR BALANCE AND LEARNING HANDLING AND CORRECTION SKILLS BY HANDBALL - Asst .Prof. Dr. Mateen Sulaiman Salih , Asst. Lec. Manal Mohammed Ahmed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Physical education is one of the educational sciences that has received increasing attention, which is an important part of the general educational process and has an advanced position in the lives of peoples and nations, as it highlights its importance in developing and developing physical and mental capabilities and improving the social and health aspects of the individual, and it also aims to reconcile its powers Physical, mental, moral and psychological, so the exercise of physical activity and physical exercises makes the individual possesses a stand-alone motor activity, and makes the body healthy able to work and produce as well as makes the mind sound able to think and assimilate as well as an interesting recreational medium, and one of the prominent and important sciences in physical education is dynamic learning What seemed to be a great interest in him through the many and recent research and studies, which made him take an organizational form and a quick link for all new developments in the scientific methods, means and methods used to increase learning. Dynamic learning aims to learn mathematical skills through the use of educational methods and appropriate and targeted methods for the success of the learning process, but from the present time interest has become better on the theoretical information not at the higher mathematical levels but in building the foundation and learning skills that are the first step and solid base in helping The athlete has to know when the assignment is performed, when it will be accomplished and what works after performance, as well as to know if the assignment has not been completed and to know how to summon and communicate the duty, and that information processing occurs through a series of mental processes in the brain where the information entered is processed in different patterns for the purpose of converting them into representations It produces outputs that differ in treatment according to many variables, and all students are subject to them in terms of physiological and psychological laws in perception and remembering, but they are not equal in their representational patterns, their methods and strategies in information processing, that the choice of cognitive and skill treatments to perform the skill for the student through simulating the representative systems For students according to the study of sensory, auditory or visual patterns (NEURAL BRAIN PROGRAMMING ) The teacher will be able to develop a curriculum and program for treatment according to each type of NEURAL BRAIN PROGRAMMING systems in the sports field, and studies and research have confirmed that there is an effect of using the methodology of information processing strategy at the skill and cognitive level.